Expanding Social Insurance Coverage in Urban China - Giles, John; Wang, Dewen; Park, Albert (World Bank, Washington, DC, 2013)
This paper first reviews the history of social insurance policy and coverage in urban China, documenting the evolution in the coverage of pensions and medical and unemployment insurance for both local residents and migrants, and highlighting obstacles to expanding coverage. The paper then uses two waves of the China Urban Labor Survey, conducted in 2005 and 2010, to examine the correlates of social insurance participation before and after implementation of the 2008 Labor Contract Law. A higher labor tax wedge is associated with a lower probability that local employed residents participate in social insurance programs, but is not associated with participation of wage-earning migrants, who are more likely to be dissuaded by fragmentation of the social insurance system. The existing gender gap in social insurance coverage is explained by differences in coverage across industrial sectors and firm ownership classes in which men and women work.